2011
DOI: 10.1039/c0ob00714e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of 5-lipoxygenase translocation inhibitors from acylnitroso hetero-Diels–Alder cycloadducts

Abstract: Acylnitroso cycloadducts have proven to be valuable intermediates in the syntheses of a plethora of biologically active molecules. Recently, organometallic reagents were shown to open bicyclic acylnitroso cycloadducts and, more interestingly, the prospect of highly regioselective openings was raised. This transformation was employed in the synthesis of a compound with excellent inhibitory activity against 5-lipoxygenase ((±)-4a, IC50 51 nM), an important mediator of inflammation intimately involved in a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…These studies support the conclusion that 5-LOX is an important target; they show that blockade of 5-LOX inhibits colon cancer cell proliferation both in vitro and in vivo and they suggest that 5-LOX inhibitors may provide a beneficial chemopreventive therapy in colon cancer [83]. Bolger et al [84] recently developed (±)-4-acylnitroso cycloadducts with excellent inhibitory activity against 5-LOX. One compound was tested in vivo in an established colon cancer APC −Min mouse model and was shown to have antitumorigenic properties.…”
Section: -Lox Inhibitors For Crc Preventionsupporting
confidence: 60%
“…These studies support the conclusion that 5-LOX is an important target; they show that blockade of 5-LOX inhibits colon cancer cell proliferation both in vitro and in vivo and they suggest that 5-LOX inhibitors may provide a beneficial chemopreventive therapy in colon cancer [83]. Bolger et al [84] recently developed (±)-4-acylnitroso cycloadducts with excellent inhibitory activity against 5-LOX. One compound was tested in vivo in an established colon cancer APC −Min mouse model and was shown to have antitumorigenic properties.…”
Section: -Lox Inhibitors For Crc Preventionsupporting
confidence: 60%
“…In the past few years, effort has been made in generating and refining 5-LOX inhibitors for the treatment of inflammation, allergies, cardiovascular disease, and cancer [154]. Recently, a new generation of 5-LOX inhibitors has been described and shown to selectively inhibit 5-LOX activity in vitro as well as to decrease the incidence of adenoma in APCmin/+ mice [155]. In addition, novel di-O-prenylated chalcone derivatives have been generated and shown to be potent 5-LOX inhibitors in vivo and to inhibit human breast cancer cell proliferation in vitro [156].…”
Section: Single Versus Dual Inhibition Of Cox and Lox In Tumorigenesismentioning
confidence: 99%
“…We recently reported synthetic variations of the metal binding groups and found that representative compounds potently inhibit 5-lipoxygenase translocation 5. Herein, report on synthetic elaboration of analogs containing substituents on the distal ring of the diaryl ether.…”
mentioning
confidence: 99%
“…The route not only employed regioselective ring opening alkylation chemistry, but also copper-mediated condensation of a phenol and arylboronic acids, as well as a useful one-pot, alumina-mediated transcarbamoylation. Based on our previous studies,5 these compounds are expected to possess significant inhibitory activity against the 5-lipoxygenase enzyme.…”
mentioning
confidence: 99%